Comparative genomics of human brain and immune gene preservation across species - Xiao Liang; Andrew F. Teich; Lenwood S. Heath (PLoS ONE, 2026)
The study of human gene evolution along primate and non-primate lineages has attracted increasing attention. Previous research demonstrated associations between the origin of genes and their expression in various tissues, including human-specific genes contributing to the brain. However, the relationship between gene tissue expression and their existence in evolutionary history has rarely been systematically examined from a phylogenetic perspective. In this study, we analyzed 1360 human genes highly expressed in the brain and/or the immune system, along with their distribution in 31 non-human primate species and 4 non-primate species. Two control sets were included for comparison: a randomly selected set of 295 human genes, and a set of 369 human genes each representing a distinct HGNC gene family. We discovered that compared to random and immune-related genes (genes highly expressed in immune system), brain genes (genes highly expressed in brain) have earlier origins, predating primates, and have been preserved across various primate species. We also show that these earlier origins are unlikely to be due to genes that are widely highly expressed in many tissues. Moreover, genes highly expressed in both the brain and immune system display a tendency toward early origin, consistent with other brain genes. This observation indicates that genes highly expressed in both systems are more likely to begin with high expression in the brain, subsequently acquiring high expression in immune tissues, rather than vice versa. We investigated the brain and immune-related genes that are estimated to have emerged among primates, as well as genes that originated before primates but are absent in certain primate clades. Genes in the latter group were either highly expressed across more than ten tissues or specifically expressed in no more than two organ systems, suggesting that these genes may be either broadly essential or highly specialized, performing specific functions in a few systems.